2018
DOI: 10.4102/sajpsychiatry.v24.i0.1162
|View full text |Cite
|
Sign up to set email alerts
|

A study of medical professionals’ perspectives on medicines containing codeine in South Africa

Abstract: BackgroundMisuse of codeine available on prescription and over-the-counter (OTC) has been highlighted as a potential problem in South Africa.ObjectiveTo examine the perceptions of medical professionals regarding codeine use (prescribed and OTC), misuse, dependence and treatment options in South Africa.MethodData for the study were obtained using a sample of medical professionals obtained through random and convenience sampling. A quantitative methodology was employed using a structured self-administered questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 13 publications
(13 reference statements)
0
42
0
Order By: Relevance
“…This study has also shown that consumer's attitude and behaviour as an additional challenge faced by health care providers. This translate into poor protocol implementation for most health care providers who shun away from conflicts with patients or costumers at pharmacy and weak enforcement of regulations and policies has being reported (16). On other hand, consumers' denial and dishonesty adds to the burdened health system gaps such as lack of screening tools (16), lack of monitoring systems (18), poor supervision (16) therefore perpetuating drug diversion problem.…”
Section: Participants Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study has also shown that consumer's attitude and behaviour as an additional challenge faced by health care providers. This translate into poor protocol implementation for most health care providers who shun away from conflicts with patients or costumers at pharmacy and weak enforcement of regulations and policies has being reported (16). On other hand, consumers' denial and dishonesty adds to the burdened health system gaps such as lack of screening tools (16), lack of monitoring systems (18), poor supervision (16) therefore perpetuating drug diversion problem.…”
Section: Participants Characteristicsmentioning
confidence: 99%
“…In South Africa there is limited data on drug diversion, misuse and abuse. The misuse of opioids in the form of codeine containing products has recently being documented as most commonly accessed in local pharmacies (5,(16)(17)(18)(19)(20)(21)(22). Tolerance, dependence and addiction of codeine can develop very rapidly (11).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations